Đáp án :
Phương trình có tập nghiệm `S={-3; 0}`
Giải thích các bước giải :
`+)Không có Đkxđ`
`(x^4+3x^3+9x-9)/(x^2+3)=-3`
`<=>(x^4+3x^3+9x-9)/(x^2+3)+3=0`
`<=>(x^4+3x^3+9x-9)/(x^2+3)+(3(x^2+3))/(x^2+3)=0`
`<=>(x^4+3x^3+3x^2+9x-9+9)/(x^2+3)=0`
`<=>(x^4+3x^3+3x^2+9x)/(x^2+3)=0`
`<=>x^4+3x^3+3x^2+9x=0`
`<=>x^3(x+3)+3x(x+3)=0`
`<=>x(x+3)(x^2+3)=0`
Vì `x^2 ≥ 0 => x^2+3 ≥ 3 => x^2+3 > 0 => x^2+3 \ne 0`
`=>x(x+3)=0`
`<=>`\(\left[ \begin{array}{l}x=0\\x+3=0\end{array} \right.\)
`<=>`\(\left[ \begin{array}{l}x=0 (tmđk)\\x=-3 (tmđk)\end{array} \right.\)
Vậy : Phương trình có tập nghiệm `S={-3; 0}`